2021
DOI: 10.1161/circulationaha.120.052380
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin on Presentation to Rule Out Myocardial Infarction: A Stepped-Wedge Cluster Randomized Controlled Trial

Abstract: Background: High-sensitivity cardiac troponin assays enable myocardial infarction to be ruled out earlier, but the safety and efficacy of this approach is uncertain. We investigated whether an early-rule out pathway is safe and effective for patients with suspected acute coronary syndrome. Methods: We performed a stepped-wedge cluster randomized controlled trial in the Emergency Departments of seven acute care hospitals in Scotland. Consecutive patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 52 publications
(87 reference statements)
4
78
1
2
Order By: Relevance
“…The discovery that low troponin concentrations identify patients who are at low risk of cardiac events has led to the development of accelerated care pathways for patients with suspected acute coronary syndrome ( 6 , 20 , 21 , 22 ). Recent evidence from randomized controlled trials has shown that implementation of this approach is safe and effective at substantially reducing length of hospital stay and the proportion of patients who require hospital admission ( 23 ). In contrast, among patients in whom myocardial infarction has been ruled out, an intermediate troponin concentration within the normal reference range is associated with a 5-10× higher medium- and long-term risk of adverse cardiac events compared with those with a low (<5 ng/L) troponin concentration ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery that low troponin concentrations identify patients who are at low risk of cardiac events has led to the development of accelerated care pathways for patients with suspected acute coronary syndrome ( 6 , 20 , 21 , 22 ). Recent evidence from randomized controlled trials has shown that implementation of this approach is safe and effective at substantially reducing length of hospital stay and the proportion of patients who require hospital admission ( 23 ). In contrast, among patients in whom myocardial infarction has been ruled out, an intermediate troponin concentration within the normal reference range is associated with a 5-10× higher medium- and long-term risk of adverse cardiac events compared with those with a low (<5 ng/L) troponin concentration ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Cohort-2, there was a clinical recommendation to collect samples 3 h apart as per the Canadian Institutes of Health Research funded grant and study protocol [24]. As the diagnostic parameters have been published for the ESC 0/1 h algorithm cutoffs (sensitivity/NPV/specificity/PPV of 97.8%/99.4%/91.3%/50%) in Cohort-2 [24], the 0/2 h algorithm cutoffs were assessed (as the ESC recommends to use the 0/2 h algorithm as an alternative to the 0/1 h algorithm) [3], as well as the High-STEACS pathway [14] and COMPASS-MI algorithm [5] in both cohorts (see Table 1 for details of the algorithms). For COMPASS-MI, physicians can select different cutoffs as detailed in the original publication and using the web-based calculator (https://compass-mi.com/ accessed on 26 April 2021) [5].…”
Section: Laboratory Testing and Algorithms Evaluatedmentioning
confidence: 99%
“…Others have proposed predictive values be used [10], with the following diagnostic estimates being evaluated in studies: sensitivity ≥ 99% or negative predictive value (NPV) ≥ 99.5% for rule-out and specificity ≥ 90% or positive predictive value (PPV) ≥ 75% for rule-in [11][12][13]. Many algorithms have been developed and implemented based mainly on predictive values, and despite the number of published algorithms increasing, there are few headto-head comparison studies performed in the same cohorts with even fewer algorithms validated in external populations to assess generalizability [3,10,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These guideline recommendations are supported by recent randomised trials that have provided new insights into the safety and effectiveness of these pathways in clinical practice. [5][6][7] Multiple pathways have been proposed that vary according to the thresholds used for decision-making and timing of sampling. Implementing a validated pathway could save healthcare resources and improve the safe delivery of patient care.…”
Section: Introductionmentioning
confidence: 99%